2022
DOI: 10.3390/su14137532
|View full text |Cite
|
Sign up to set email alerts
|

Identifying the Barriers to Sustainable Management of Construction and Demolition Waste in Developed and Developing Countries

Abstract: The construction industry is a vital part of every nation’s economy. Construction activities influence the social, environmental, and economic aspects of sustainability. There are so many barriers to sustainable construction and demolition waste management (C&DWM). This study aims to identify barriers for effective sustainable C&DWM in developed and developing countries. To achieve the objective, 11 barriers have been selected and identified based on an excessive and comprehensive literature review, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 72 publications
0
11
0
Order By: Relevance
“…Furthermore, green building practices in these countries often face financial constraints and a lack of incentives [26,27]. Additionally, the building codes and regulations in these countries may not be as stringent as those in developed countries [28]; therefore, creating regulatory constraints. Educational challenges also affect the availability of skilled professionals, and technical constraints limit equipment and material options.…”
Section: Building Codes and Green Building Rating Systems For The Car...mentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, green building practices in these countries often face financial constraints and a lack of incentives [26,27]. Additionally, the building codes and regulations in these countries may not be as stringent as those in developed countries [28]; therefore, creating regulatory constraints. Educational challenges also affect the availability of skilled professionals, and technical constraints limit equipment and material options.…”
Section: Building Codes and Green Building Rating Systems For The Car...mentioning
confidence: 99%
“…Additionally, a lack of public participation in political processes or conflicting interests among political actors can also limit progress toward the development of effective regulation [14]. Even where effective regulations exist, there remain challenges to fully and effectively implementing and enforcing regulations [16,27,28] due to factors such as lack of knowledge and skills, limited training of professionals, and corruption.…”
Section: Political Barriersmentioning
confidence: 99%
“…According to research [4,5], the effective and sustainable development of the field of construction waste management depends on legislative and informational support, financial support, clear rules for regulating the behavior of market participants. Noting the practical significance of the research results regarding the development of cooperation, integrated waste management [4], the formation of certainty and trust between interested parties [5], the mechanisms of formation of a set of such relations are not defined in the cited works. The role of the state in the management of construction waste is emphasized in study [6], the results of which confirmed the need for legislative incentives.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
“…The generalization of the results of scientific research [1][2][3][4][5][6][7][8][9][10][11] led to the conclusion that the task to form an effective mechanism for stimulating the growth of the level of processing of construction waste remains unresolved and requires further research.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
“…As of now, the Kingdom of Saudi Arabia has not established any formal laws or a nationwide strategy for CE [28]. There is a significant institutional fragmentation and insufficient attention to construction and demolition waste [29]. According to Ibrahim and Shirazi [30], neither Saudi Arabia nor the GCC have a holistic policy in place regarding CE.…”
Section: Introductionmentioning
confidence: 99%